(untitled) (World of finance, 2025)
Introduction. The financial security of the state becomes a key priority of economic policy, and the development of an innovative economy depends on the stability of the domestic economic system, its investment attractiveness and ability to compete. A significant role in this process is played by individuals and households, on the effective and rational use of financial resources of which the development of the country’s economy, and therefore its financial security, depends. In view of the need to ensure the country’s financial security, the issue of developing financial literacy of citizens as subjects of financial relations, capable of generating sufficient financial and investment resources for expanded reproduction and economic growth of the country, as well as acting as end consumers of goods and services, is being brought up to date. The purpose of the article is to generalize theoretical approaches to defining the concepts of “financial security of the country” and “financial security of households” in terms of identifying their internal relationships and interdependence; to justify the direct and indirect influence of all components of the country’s financial security on the financial security of households through the active use of methods and tools of the appropriate mechanism for ensuring its financial stability; to outline the main vectors of influence of the level of financial literacy of citizens on the financial security of the country, to argue the need to increase the financial literacy of our compatriots. Results. The economic content of the country’s financial security, the influence of its components on the financial security of households with the help of direct and indirect influence of methods, tools and levers of the financial security mechanism are disclosed; the main challenges to the financial security of the country were identified and threats to the financial security of households were identified; the close relationship between the level of financial literacy of citizens and the financial security of the country is indicated; identified approaches to increase the level of financial literacy of Ukrainians as a priority direction for ensuring the country’s financial security. Conclusions. According to the results of the study, it was concluded that the financial literacy of citizens and the financial security of the country are closely related, since the level of knowledge and skills of the population in managing their own finances, their financial behavior directly affects the economic stability of both individual households and the state in a whole. The use of an integrated interdisciplinary approach in the development of measures and programs to increase the level of financial literacy of the population will contribute to the formation of an effective mechanism for ensuring the financial security of households and the financial security of the country as a whole.